The book of Amos - Carroll R., M. Daniel (New International Commentary on the Old Testament (NICOT), 2020)
Intro -- Title Page -- Copyright -- Dedication -- Contents -- List of Excursuses -- General Editor's Preface -- Author's Preface -- Abbreviations -- Select Bibliography -- Introduction -- I. Historical Background -- A. The Challenge of the Data -- B. The Date of the Ministry of the Prophet Amos -- C. The International Context -- D. The Socioeconomic Context in Israel -- II. Authorship -- A. The Prophet as Authorial Voice -- B. The Person of Amos -- III. Composition, Structure, and Poetics -- A. The Book as the Result of an Editorial Process -- B. The Authenticity and Unity of the Book -- 1. The Biographical and Contextual Argument -- 2. The Book as a Literary Unity -- IV. Religion and Theology in the Book of Amos -- A. The Religious Context -- 1. The Significance of "Official Religion" and "Popular Religion" -- 2. The Critique of Religion and the Cult -- B. The Theology of the Book of Amos -- 1. Theological Traditions -- 2. Theological Message -- V. Amos in Early Judaism and the New Testament -- VI. The Message of Amos for Today -- VII. The Text -- Text and Commentary -- I. Preface (1:1-2) -- A. Superscription (1:1) -- B. Summary Oracle (1:2) -- II. The Oracles Against the Nations (1:3-2:16) -- A. Oracle against Damascus (1:3-5) -- B. Oracle against Philistia (1:6-8) -- C. Oracle against Tyre (1:9-10) -- D. Oracle against Edom (1:11-12) -- E. Oracle against Ammon (1:13-15) -- F. Oracle against Moab (2:1-3) -- G. Oracle against Judah (2:4-5) -- H. Oracle against Israel (2:6-16) -- 1. Opening Formula and Statement of Israel's Transgressions (2:6-8) -- 2. Rejection of the Gracious Acts of Yahweh (2:9-12) -- 3. Announcement of Judgment (2:13-16) -- III. The Words of God and the Prophet to Israel (3:1-6:14) -- A. Divine Exposure of Israel's Guilt (3:1-4:13) -- 1. Two Tales of One City (3:1-4:3) -- 2. Love Can Be Blind (4:4-13).